Mixed cryoglobulinemia-associated Sjögren's syndrome leading to spontaneous rupture of the kidney: a case report - Haddiya I (International Medical Case Reports Journal, 2016)
Intissar Haddiya,1 Hakim Hamzaoui,1 Zitouna Alhamany,2 Fatime-zohra Berkchi,1 Hakima Rhou,1 Loubna Benamar,1 Naima Ouzeddoun,1 Rabea Bayahia1 1Department of Nephrology-Dialysis-Renal Transplantation, Ibn Sina University Hospital, Rabat, Morocco; 2Department of Pathology, Rabat Children's Hospital, Ibn Sina University Hospital, Rabat, Morocco Background: Spontaneous rupture of the kidney is uncommon and is mainly caused by renal tumors. Only a few cases are caused by vasculitis. We report here the first case of spontaneous rupture of kidney resulting from mixed cryoglobulinemia. Case presentation: A 44-year-old man presented with sudden onset of fever, acute pulmonary edema, left flank abdominal pain unassociated with trauma, and rapidly progressive renal failure requiring dialysis. Computed tomography of the abdomen revealed a large perirenal hematoma of the left kidney. During conservative surgery, the patient underwent renal biopsy that showed renal vasculitis and membranoproliferative glomerulonephritis with intracapillary microthrombi. Tests were positive for mixed cryoglobulinemia caused by Sjögren's syndrome. The patient was better after immunosuppressive therapy, with the disappearance of clinical symptoms and the recovery of baseline renal function. Conclusion: We report on this case and discuss a possible link between spontaneous rupture of kidney and mixed cryoglobulinemia-associated Sjögren's syndrome. Keywords: mixed cryoglobulinemia, Sjögren's syndrome, spontaneous rupture of kidney, renal hematoma, Wünderlich syndrome